2011
DOI: 10.1159/000323501
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Lipopeptides Bacillomycin D and Fengycin in Antagonism of <i>Bacillus amyloliquefaciens</i> C06 towards <i>Monilinia fructicola</i>

Abstract: In previous studies, Bacillus amyloliquefaciens C06 has been proven to be effective in controlling brown rot of stone fruit caused by Monilinia fructicola. When tested in vitro, cell-free filtrate of B. amyloliquefaciens C06 significantly inhibited mycelial growth and conidial germination of the fungal pathogen. This study aimed to determine the role of the antifungal compound(s) in the cell-free filtrate of B. amyloliquefaciens C06 by an approach combining a DNA-based suppression subtractive hybridization (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 79 publications
4
55
0
Order By: Relevance
“…Most were not relevant. Few (Coutte et al, 2010;Liu et al, 2011;Tabbene et al, 2011;Raaijmakers et al, 2010;Thasana et al, 2010) concerned the antifungal or antimicrobial activities of Bacillus species and indicated that at least part of the activity was due to the peptidolipides (e.g., surfactin, fengicin, iturin) which are also suspected of being involved in the rare foodpoisoning cases caused by Bacillus species other than Bacillus cereus (EFSA, 2008a). Such Bacillus strains producing these lipopeptides would not meet the qualification "Absence of toxigenic activity" specified for Bacillus species in the QPS approach.…”
Section: Bacillus Pumilus (Plant Protection Products)mentioning
confidence: 99%
“…Most were not relevant. Few (Coutte et al, 2010;Liu et al, 2011;Tabbene et al, 2011;Raaijmakers et al, 2010;Thasana et al, 2010) concerned the antifungal or antimicrobial activities of Bacillus species and indicated that at least part of the activity was due to the peptidolipides (e.g., surfactin, fengicin, iturin) which are also suspected of being involved in the rare foodpoisoning cases caused by Bacillus species other than Bacillus cereus (EFSA, 2008a). Such Bacillus strains producing these lipopeptides would not meet the qualification "Absence of toxigenic activity" specified for Bacillus species in the QPS approach.…”
Section: Bacillus Pumilus (Plant Protection Products)mentioning
confidence: 99%
“…Other CLPs such as kurstarkin have also identified 19 . Both iturins and fengycins are known to have antifungal activities, and fengycin more strongly inhibits the growth of filamentous fungi 20 ; however, little is known about the interfacial properties of these CLPs, especially fengycins. Singh et al investigated the carbon-source-dependent surface tension reduction by Bacillus amylofaciens strain AR2.…”
Section: Introductionmentioning
confidence: 99%
“…This peptide sequence causes bacillomycin D to adopt an unconventional γ i -turn conformation between the CO group of the Ser6 residue and the NH group of the β-amino acid residue. Studies into the interfacial properties of bacillomycin D suggested that the protonable Glu residue plays a significant role in its solubilisation into the lipid bilayer that bacillomycin D plays a significant role in fungal inhibition Liu et al, 2011). When bacillomycin D synthesis is combined with the synthesis of fengycin, a much greater inhibition is observed against fungi suggesting that these two compounds have a synergistic effect .…”
Section: Lipopeptidesmentioning
confidence: 99%
“…The gene cluster mln is responsible for macrolactin biosynthesis in which it is assembled from acetate/malonate precursors (Schneider et al, 2007). Studies into the antimicrobial activities of macrolactin have shown that its inhibitory effect is bacteriostatic, not bactericidal (Romero-Tabarez With the accumulation of such a large complement of antimicrobial compounds, it is unsurprising to discover that B. amyloliquefaciens has been used as a probiotic in a number of different circumstances Liu et al, 2011). The antimicrobial action of each compound contributes to the broad spectrum of inhibition.…”
Section: Polyketidesmentioning
confidence: 99%
See 1 more Smart Citation